2000
DOI: 10.1007/s004230050268
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytolytic activity of intestinal intraepithelial lymphocytes in patients with Crohn's disease

Abstract: In Crohn's disease, the functional and phenotypic changes of T cells are limited to lymphocytes of the intestinal mucosa. Furthermore, it is conceivable that the increased cytolytic activity of IEL contributes to the tissue damage in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…In agreement with the reported increase in CD31 CD81 IEL in the rectal mucosa of Crohn's disease patients (30) and enhanced cytolytic activity of these cells (31), IL10(2/2) mice treated with the control diet had the highest proportion of CD31 IEL, most of them also expressing the CD8 phenotype. This was associated with a high incidence of colitis.…”
Section: Discussionsupporting
confidence: 84%
“…In agreement with the reported increase in CD31 CD81 IEL in the rectal mucosa of Crohn's disease patients (30) and enhanced cytolytic activity of these cells (31), IL10(2/2) mice treated with the control diet had the highest proportion of CD31 IEL, most of them also expressing the CD8 phenotype. This was associated with a high incidence of colitis.…”
Section: Discussionsupporting
confidence: 84%
“…In this context, our finding that in CrD and UC the number of CD8 ϩ CD11a ϩ NF-B ϩ cells is significantly increased compared with controls was interesting, confirming the previously described enhanced cytolytic activity of intestinal intraepithelial lymphocytes in patients with CrD ( Fig. 6) (24).…”
Section: Cd4supporting
confidence: 77%
“…intestinal mucosa of Crohn's disease patients, and it has been suggested that increased cytolytic activity of CD8 + T cells in the intraepithelial compartment of the patients may be involved in the induction of epithelial tissue damage (Nussler et al 2000, Honma et al 2001, Melgar et al 2002. The findings from studies in giardiasis demonstrating that CD8 + lymphocytes are implicated in brush border injury and malfunction are consistent with this hypothesis.…”
mentioning
confidence: 84%